.NET Patterns : Architecture, Design, and Process - Thilmany, Christian (Addison-Wesley Professional, 2003)
The complete software developer's guide to working in .NET environments Praise for .NET Patterns: "Was both insightful and comprehensive. It's great to see these patterns presented within the context of many architectural dilemmas facing the vastly interconnected enterprise. Web service architects are sure to see enormous value in this text."--Ed Draper, Microsoft Patterns have proven to be practical tools for the programmer who knows how to use them. In .NET Patterns, distributed computing and .NET expert Christian Thilmany presents both an introduction to patterns for programmers working in the .NET environment and a library of patterns unique to the .NET platform. Part of John Vlissides' critically acclaimed Addison-Wesley Software Patterns Series, .NET Patterns extends the proven concept of design patterns into the arena of .NET design and development. Now, .NET developers can depend on patterns to provide solutions to recurring problems in software design. In addition to covering both lower and higher level programming with patterns, this book also includes helpful primers on XML and web services, as well as thorough coverage of debugging, exceptions, error handling, and architecture. Whether you're working in .NET environments or transitioning to .NET environments, you'll find .NET Patterns a comprehensive resource for software solutions.